Research on self-reflection in teenage years (Actual Problems of Psychology in Educational Institutions, 2021)
The article is devoted to the study of reflection in teenage years.We have reviewed and analyzed scientific sources on this topic. The viewsof scientists on this phenomenon and its significance in teenage years wereconsidered. Also, diagnostics of the level of development of reflection inmodern teenagers was implemented using the method of determining thelevel of reflexivity by A. V. Karpova, V. V. Ponomareva. Further analysis ofthe diagnostic results allowed us to draw conclusions regarding the existinglevel of self-reflection in teenage years. Also, psychological and pedagogicalrecommendations were developed to increase the level of self-reflection inmodern teenagers.
Keywords: : reflection, self-reflection, reflexivity, teenage years, personality development, consciousness